Odpowiedzi

2010-01-11T21:55:53+01:00
X - 1 + 2 ( x - 2 ) + 3 ( x - 3 ) = 4 ( x - 2 )
x-1+2x-4+3x-9=4x-8
2x=6
x=3
Sprawdzenie: 3-1+2(3-2)+3(3-3)=4(3-2)
2+6-4+9-9=12-8
4=4

- 3 ( x - 2 ) + 3 ( x - 3 ) = 4 ( x - 2 )
-3x+6+3x-9=4x-8
x= 5/4 = 1.25
Sprawdzenie: -3(1,25-2) +3 (1,25-3)=4(1,25-2)
-3,75+6+3,75-9=5-8
-3=-3
2010-01-11T22:00:46+01:00
X - 1 + 2 ( x - 2 ) + 3 ( x - 3 ) = 4 ( x - 2)
x-1+2x-4+3x-9=4x-8
x+2x+3x-4x=1+4+9-8
2x=6
x=6/2
x=3


- 3 ( x - 2 ) + 3 ( x - 3 ) = 4 ( x - 2 )
-3x+6+3x-9=4x-8
-3x+3x-4x=-6-8
-4x=-14
x=-14/-4
x=3,5
2010-01-11T22:07:40+01:00
X - 1 + 2 ( x - 2 ) + 3 ( x - 3 ) = 4 ( x - 2 )
x - 1 + 2x - 4 + 3x - 9 = 4x - 8
2x = 6
x = 3

3-1+2(3-2)+3(3-3)=4(3-2)
3-1+2=4
4=4

-3(x-2)+3(x-3)=4(x-2)
-3x+6+3x-9=4x-8
-4x=-5
x=5/4

-3(5/4-2)+3(5/4-3)=4(5/4-2)
2,25-5,25=-3
-3=-3